2008
DOI: 10.1088/0957-4484/19/29/295203
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanowire-based solar cells

Abstract: The fabrication of silicon nanowire-based solar cells on silicon wafers and on multicrystalline silicon thin films on glass is described. The nanowires show a strong broadband optical absorption, which makes them an interesting candidate to serve as an absorber in solar cells. The operation of a solar cell is demonstrated with n-doped nanowires grown on a p-doped silicon wafer. From a partially illuminated area of 0.6 cm(2) open-circuit voltages in the range of 230-280 mV and a short-circuit current density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
253
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(264 citation statements)
references
References 13 publications
6
253
1
4
Order By: Relevance
“…Others have reported sub-bandgap absorption in Au-catalyzed, VLS-grown Si wire arrays (up to ~0.6 at these wavelengths), and this has been primarily attributed to the presence of surface states, defects, or catalyst metal particles [3][4][5] . It is well-known that certain defects or impurities introduce energy levels or bands within a semiconductor's bandgap, and can give rise to extrinsic (trap-assisted) sub-bandgap absorption.…”
Section: Sub-bandgap Absorptionmentioning
confidence: 99%
“…Others have reported sub-bandgap absorption in Au-catalyzed, VLS-grown Si wire arrays (up to ~0.6 at these wavelengths), and this has been primarily attributed to the presence of surface states, defects, or catalyst metal particles [3][4][5] . It is well-known that certain defects or impurities introduce energy levels or bands within a semiconductor's bandgap, and can give rise to extrinsic (trap-assisted) sub-bandgap absorption.…”
Section: Sub-bandgap Absorptionmentioning
confidence: 99%
“…Nanowire arrays can potentially provide a unique advantage due to their anti-reflective and light trapping properties. Silicon NW arrays of only several microns in length have been noted for their strong broadband optical absorption and dark visual appearance [25,34]. Numerical studies on the optical properties of disordered NW arrays by diffuse scattering [35] and ordered vertical arrays by specular reflection [36] have demonstrated that NW arrays have distinct absorption spectra from their thin fi lm counterparts.…”
Section: ) Reduced Optical Reflection and Enhanced Absorptionmentioning
confidence: 99%
“…In addition to factors such as material and manufacturing costs [1][2][3], novelty of non-planar solar cell architectures is grounded in the idea that some non-planar devices decouple optical and electronic path lengths [4] and, therefore, offer opportunities to alter the competing roles of charge carrier collection and recombination within a device, which limit efficiency for planar cells with low charge carrier mobility and lifetime. In recent years, a number of unconventional, non-planar solar cell designs have been proposed, and some experimentally fabricated [4][5][6][7][8][9][10][11][12][13], in efforts to increase energy conversion efficiencies. To date, however, the planar solar cell architecture still holds all efficiency records over its non-planar counterparts [14].…”
Section: Introductionmentioning
confidence: 99%